Doubts on Avicenna : a study and edition of Sharaf al-Din al-Mas'udi's commentary on the Isharat - Shihadeh, Ayman. (Islamic Philosophy, Theology and Science. Texts and Studies, 2016)
In Doubts on Avicenna , Ayman Shihadeh brings to light an important new source, which marks a key moment of transition in twelfth-century Arabic philosophy. Sharaf al-Dīn al-Masʿūdī's al-Mabāḥith wa-l-Shukūk ʿalā l-Ishārāt ( Investigations and Objections on the Pointers ) offers major insight into the dialectic between the two traditions of Avicennan philosophy and rational theology, particularly Ashʿarism, which by the end of the century culminates in the systematic philosophical theology of Fakhr al-Dīn al-Rāzī. Inaugurating the long and distinguished commentarial tradition on Avicenna's Ishārāt ( Pointers ), al-Masʿūdī's Shukūk uniquely consists of aporias on selected passages, as opposed to exegesis. This monograph provides an overview and the first critical edition of the text, and in-depth case studies of metaphysical aporias and their Avicennan background.